Update on giant cell arteritis (GCA) - Clifford, Alison (Henry Stewart Talks, 2025)
New classification criteria for GCA, PET/CT and temporal artery ultrasound imaging in GCA, Prognosis, Glucocorticoid dosing regimen, Steroid-sparing treatment